Reconciliation: Divine and Human: 2 Corinthians 5 from a Theological Perspective - Chalamet, Christophe (The ecumenical review, 2021)
Reconciliation is one of the key motifs used by the apostle Paul and other New Testament authors influenced by him as they sought to express the significance and reach of God’s salvific act in Jesus Christ. To reflect on the theme of reconciliation means reflecting on the very centre of the good news. This theme is not one aspect of the gospel alongside others. Rather, it suffuses the apostolic message as a whole. The theme of reconciliation lies at the very heart of Christian theology: it expresses the overarching intent of God in the face of human violence and conflict. If we follow the apostle Paul’s key text on this theme, we must note that the root of reconciliation lies not in our actions but exclusively in God’s act. We, as people who are as pilgrims on this earth, are not merely agents of reconciliation, but also those who are and who remain in dire need to receive the gift of reconciliation.